Redefining the DNA-Binding Domain of Human XPA - Sugitani, Norie (American Chemical Society, 2014)
[Image: see text] Xeroderma pigmentosum complementation group A (XPA) protein plays a critical role in the repair of DNA damage via the nucleotide excision repair (NER) pathway. XPA serves as a scaffold for NER, interacting with several other NER proteins as well as the DNA substrate. The critical importance of XPA is underscored by its association with the most severe clinical phenotypes of the genetic disorder Xeroderma pigmentosum. Many of these disease-associated mutations map to the XPA(98–219) DNA-binding domain (DBD) first reported ∼20 years ago. Although multiple solution NMR structures of XPA(98–219) have been determined, the molecular basis for the interaction of this domain with DNA is only poorly characterized. In this report, we demonstrate using a fluorescence anisotropy DNA-binding assay that the previously reported XPA DBD binds DNA with substantially weaker affinity than the full-length protein. In-depth analysis of the XPA sequence suggested that the original DBD construct lacks critical basic charge and helical elements at its C-terminus. Generation and analysis of a series of C-terminal extensions beyond residue 219 yielded a stable, soluble human XPA(98–239) construct that binds to a Y-shaped ssDNA–dsDNA junction and other substrates with the same affinity as the full-length protein. Two-dimensional (15)N–(1)H NMR suggested XPA(98–239) contains the same globular core as XPA(98–219) and likely undergoes a conformational change upon binding DNA. Together, our results demonstrate that the XPA DBD should be redefined and that XPA(98–239) is a suitable model to examine the DNA binding activity of human XPA.